Analysis of the pathogenic variability and genetic diversity of the plantparasitic nematode Radopholus similis on bananas - Plowright, R.; Dusabe, J.; Coyne, Danny L.; Speijer, P. (Brill, 2013)
Radopholus similis is responsible for huge production losses of banana in Uganda, where a large proportion of the population are reliant on cooking banana as their main staple crop. Assessment of the pathogenic and genetic variability of seven populations of R. similis originating from banana plantations in Uganda demonstrated that their virulence on Musa cultivars differed, displaying pathotype-like variation. Using RAPD and AFLP techniques the populations could be grouped into two putative genomic groups, which corresponded with R. similis relative pathogenicity. Most, but not all, populations were able to reproduce and damage roots on the two widely confirmed sources of resistance, Yangambi km5 and Pisang Jari Buaya. Studies using RAPD techniques furthermore revealed putative markers for nematode virulence. Variation in virulence of R. similis populations was also demonstrated at the regional (Africa) level. Phylogenetic analysis most closely associated the Uganda populations with populations from Sri Lanka, indicating their likely source of origin. However, genetic variability between Uganda populations also indicate that R. similis was probably introduced into Uganda on separate occasions from different sources, which may help to explain the causes of variability in banana decline in Uganda. The results of this study have clear implications for the development and deployment of sustainable nematode management practices based on the use of resistance, which could help underpin ongoing management initiatives.